Effect of sodium bicarbonate on prolonged running performance: A randomized, double-blind, cross-over study - Freis, Tanja; Hecksteden, Anne; Such, Ulf; Meyer, Tim (PLOS ONE, 2017)
Background The ability to sustain intense exercise seems to be partially limited by the body’s capability to counteract decreases in both intra- and extracellular pH. While the influence of an enhanced buffering capacity via sodium bicarbonate (BICA) on short-term, high-intensity exercise performance has been repeatedly investigated, studies on prolonged endurance performances are comparatively rare, especially for running. The aim of the following study was to assess the ergogenic effects of an oral BICA substitution upon exhaustive intensive endurance running performance. Method In a double-blind randomized cross-over study, 18 trained runners (VO2peak: 61.2 ± 6.4 ml•min-1•kg-1) performed two exhaustive graded exercise tests and two constant load tests (30 main at 95% individual anaerobic threshold (IAT) followed by 110% IAT until exhaustion) after ingestion of either sodium bicarbonate (BICA) (0.3 g/kg) or placebo (4 g NaCl) diluted in 700 ml of water. Time to exhaustion (TTE) in the constant load test was defined as the main outcome measure. Throughout each test respiratory gas exchange measurements were conducted as well as determinations of heart rate, blood gases and blood lactate concentration. Results TTE in the constant load test did not differ significantly between BICA and placebo conditions (BICA: 39.6 ± 5.6 min, placebo: 39.3 ± 5.6 min; p = 0.78). While pH in the placebo test dropped to a slightly acidotic value two minutes after cessation of exercise (7.34 ± 0.05) the value in the BICA trial remained within the normal range (7.41 ± 0.06) (p < 0.001). In contrast, maximum running speed (Vmax) in the exhaustive graded exercise test was significantly higher with BICA (17.4 ± 1.0 km/h) compared to placebo (17.1 ± 1.0 km/h) (p = 0.009). The numerical difference in maximum oxygen consumption (VO2peak) failed to reach statistical significance (BICA: 61.2 ± 6.4 ml•min-1•kg-1, placebo: 59.8 ± 6.4 ml•min-1•kg-1; p = 0.31). Maximum blood lactate was significantly higher with BICA compared to the corresponding placebo test (BICA: 11.1 ± 2.3 mmol/l, placebo: 8.9 ± 3.0 mmol/l; p < 0.001). At the end of exercise, an acidotic pH value was found in both exhaustive graded exercise tests (p = 0.002). BICA caused gastrointestinal side effects in 15 patients. Conclusion Maximal performance was enhanced significantly after BICA administration. The ergogenic effect of BICA in the exhaustive graded exercise test can most likely be attributed to an increased anaerobic glycolysis that is reflected by an accumulation of lactate. However, TTE in prolonged high-intensity running was not improved. Even at the end of exercise no severe metabolic acidosis was found. Metabolic acidification as one of the dominant factors causing muscular fatigue should therefore be reconsidered. Trial registration German Clinical Trials Register (DRKS) DRKS00011284.